The Effect of the Project-Based Learning Model in Terms of Learning Styles on the Literacy and Numeracy Skills of Elementary School Students - Irma Sofiasyari; Rizky Arianty (JEES: Journal of Education and Educational Sciences, 2026)
This study aims to determine the effect of the project-based learning model in terms of learning styles on the literacy and numeracy skills of fourth-grade elementary school students in the Jamblang sub-district in 1 cluster, namely SDN 1 Wangunharja, SDN 2 Wangunharja, SDN 1 Sitiwinangun, SDN 2 Sitiwinangun, SDN 3 Sitiwinangun, SDN 1 Bojong Wetan, SDN 2 Bojong Wetan, and SDN 3 Bojong Wetan. This study used a quantitative method with a one-group pretest-posttest design. The sample in this study consisted of all 240 fourth-grade elementary school students. The research instruments consisted of a learning style questionnaire, literacy and numeracy tests with multiple choice questions for the pretest and posttest. Data collection was conducted before and after the implementation of the PjBL learning model. Data analysis included validity, reliability, normality, homogeneity, simple linear regression analysis, and paired sample t-test. The results show that each data point in the variables also meets the assumptions of normality and homogeneity. From the descriptive statistics calculation results, the hypothesis test of simple linear regression analysis and the paired sample t-test show a significant difference between the pretest and posttest scores for students' literacy and numeracy abilities. with the students' literacy ability level at the time of the pretest averaging 42.88 and the posttest score averaging 76.33, and the students' numeracy ability level at the time of the pretest averaging 43.46 and the posttest score averaging 71.21. Based on the hypothesis test, the significance value of each variable was 0.000 (<0.05), so Ho was rejected and Ha was accepted. This shows that the learning model was able to significantly improve students' literacy and numeracy skills. This study contributes novel empirical evidence by integrating Project-Based Learning assisted by e-modules with students’ learning styles in examining literacy and numeracy outcomes simultaneously at the elementary school level, an aspect that remains limited in prior quantitative pre-experimental studies.